Effects of a transformative learning theory-based health literacy enhancement program on self-management behaviors and blood pressure in adults with uncontrolled hypertension in Thailand: A cluster randomized controlled trial - Uraiwan Sasang; Decha Tamdee; Sivaporn Aungwattana; Chiraporn Tachaudomdach (Belitung Nursing Journal, 2026)
Background: Uncontrolled hypertension leads to a number of complications. To achieve effective self-management, adults with uncontrolled hypertension need health literacy to promote and maintain good health. Transformative learning is a key adult learning paradigm that supports perspective transformation, self-management, and blood pressure control. Objective: This study aimed to evaluate the effects of a Transformative Learning Theory-Based Health Literacy Enhancement Program on self-management behaviors and blood pressure among adults with uncontrolled hypertension. Methods: This cluster-randomized controlled trial was conducted at two sub-district health-promoting hospitals in northeastern Thailand. Hospitals were randomly allocated to either the experimental or control group to prevent treatment contamination. A total of 58 participants (n = 29 per group) were consecutively recruited. Data were collected between February and June 2025 using a validated Self-Management Behavior Scale and digital BP monitoring. Data were analyzed using independent- and dependent-samples t-tests and repeated-measures ANOVA, and ANCOVA was used to compare groups while controlling for baseline values. Results: At 8 and 12 weeks after the program, the experimental group had significantly higher self-management scores than the control group (t = 2.117, p = 0.039; t = 3.416, p = 0.001, respectively) and than their own baseline (F = 31.958, p < 0.001). Regarding clinical outcomes, ANCOVA revealed a significant main effect of the program on mean arterial pressure (MAP) at both 8 weeks (F(1, 55) = 9.014, p = 0.004, hp2 = 0.141) and 12 weeks (F(1, 55) = 9.133, p = 0.004,  hp2 = 0.142). The adjusted mean MAP for the experimental group was significantly lower than the control group at the final follow-up (108.90 vs. 111.37 mmHg). A significant reduction was noted for systolic blood pressure (p = 0.028) but not diastolic blood pressure. Conclusion: The study highlights the effectiveness of the program for improving self-management behaviors and systolic blood pressure. Nurses can integrate adult learning theories into health education to enhance outcomes for hypertensive patients in primary care. Trial Registry Number: Thai Clinical Trial Registry (TCTR20250202009)